Teacher Education for Peace and Harmony in the Age of Globalization - Mishra, Rachna (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2020)
Education plays a vital role to overcome many challenges and to maintain peace in the world. It is also a powerful means to ensure peace and harmony in a country. Indian scriptures have always believed in peace and harmony of body, mind and soul. Maria Mantessori also said that establishing lasting peace is the work of education. Global challenges that influence all areas of human life in the world include peace and harmony in the field of education. Peace is a state of wellbeing that is characterized by non-violence, trust, compassion and justice. This research paper will focus on how we as responsible humans can offer our future generations an education which leads to a culture of peace and harmony. It will also focus on role of education in general and teacher education in particular for developing peace and harmony. The purpose of this research paper is to create an atmosphere to learn from one another principles and methodology of peace and harmony. Teacher education needs specially to be engineered for creating safe and healthy learning environments that promote the culture of peace. The aim of the paper is to focus on the emerging concepts of teacher education for peace education with human values and its significance for teacher education reforms being pursued in the global scenario.